Natural products in drug discovery and development: Synthesis and medicinal perspective of leonurine - Li, Zhaoyi; Chen, Keyuan; Rose, Peter; Zhu, Yi Zhun (Frontiers in Chemistry, 2022)
Natural products, those molecules derived from nature, have been used by humans for thousands of years to treat ailments and diseases. More recently, these compounds have inspired chemists to use natural products as structural templates in the development of new drug molecules. One such compound is leonurine, a molecule isolated and characterized in the tissues of Herb leonuri. This molecule has received attention from scientists in recent years due to its potent anti-oxidant, anti-apoptotic, and anti-inflammatory properties. More recently researchers have shown leonurine to be useful in the treatment of cardiovascular and nervous system diseases. Like other natural products such as paclitaxel and artemisinin, the historical development of leonurine as a therapeutic is very interesting. Therefore, this review provided an overview of natural product discovery, through to the development of a potential new drug. Content will summarize known plant sources, the pathway used in the synthesis of leonurine, and descriptions of leonurine’s pharmacological properties in mammalian systems.